Monte Carlo quântico aplicado ao estudo do comportamento quântico-clássico do Neônio - CARVALHO, Thiago Milograno de (2009)
In this work we have applied Quantum Monte Carlo method at finite temperature known as Path Integral Monte Carlo (PIMC) to study the quantum-classical behavior of the Neon. We have calculated the one body density matrix as well as the atomic momentum distribution which have shown to be significantly different from the classical Maxwell- Boltzmman distribution in the range of densities and temperatures studied. The deviations from a classical gaussian are substantial but it decreases as one goes to temperatures above T = 35 K or densities below p = 20 nm−3. Furthermore, at low temperature the results show that there are more low momentum atoms than in a classical gaussian distribution.